Ovarian dysgerminoma in a pre-pubertal girl: A case report - Evance Salvatory Rwomurushaka; Patrick Amsi; Jay Lodhia (Elsevier, 2025)
Introduction: Ovarian dysgerminoma is a rare malignant germ cell tumor that rarely occurs in pre-puberal girls. Case presentation: An eight-year-old girl presented with a year-long history of progressive, painless abdominal distension and significant weight loss but without obstructive symptoms. Physical examination revealed peripheral subcentric lymphadenopathy and signs of cachexia. Her abdomen was globally distended with a large, irregular mass occupying most of the abdominal cavity. Imaging with CT of the chest and abdomen revealed a large intraperitoneal mass with regional lymphadenopathy and pulmonary metastases, initially raising suspicion for peritoneal Burkitt's lymphoma. However, an ultrasound-guided biopsy was inconclusive, prompting an exploratory laparotomy. During surgery, a large mass measuring 20 by 30 cm was excised, originating from the right ovary and fed by mesenteric vessels. The uterus, left ovary, and fallopian tube were intact and unaffected, and the peritoneum, liver, and omentum appeared smooth and without nodules.The initial postoperative course was uneventful, and histopathology confirmed the mass as an ovarian dysgerminoma. Adjuvant chemotherapy with Etoposide, Carboplatin, and Bleomycin was initiated. Unfortunately, the patient succumbed nine weeks post-surgery, following two cycles of chemotherapy, likely due to complications from hospital-acquired pneumonia and pre-existing pulmonary metastases. Conclusion: Ovarian dysgerminoma must be included in the differential diagnosis of pre-pubertal females who present with a pelvic mass.